2018
DOI: 10.1016/j.ebiom.2018.06.025
|View full text |Cite
|
Sign up to set email alerts
|

Programming and Regulation of Metabolic Homeostasis by HDAC11

Abstract: Histone deacetylases (HDACs) are enzymes that regulate protein functions by catalyzing the removal of acetyl and acyl groups from lysine residues. They play pivotal roles in governing cell behaviors and are indispensable in numerous biological processes. HDAC11, the last identified and sole member of class IV HDACs, was reported over a decade ago. However, its physiological function remains poorly understood. Here, we report that HDAC11 knockout mice are resistant to high-fat diet-induced obesity and metabolic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
85
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(88 citation statements)
references
References 45 publications
3
85
0
Order By: Relevance
“…While Sox2 might not be directly involved in the survival of differentiated cancer cells, its downstream targets like HK2 and PDK2 might be contributing in viability of the cells through their key roles in metabolic processes. Recently, HDAC11 has been also been shown to have role in metabolic homeostasis [55][56][57] . The ability of the tested compounds to downregulate the metabolic genes through HDAC11 and Sox2 might be a feature that will enable these inhibitors to eliminate stem-like and non-stem-like cancer cells simultaneously.…”
Section: Discussionmentioning
confidence: 99%
“…While Sox2 might not be directly involved in the survival of differentiated cancer cells, its downstream targets like HK2 and PDK2 might be contributing in viability of the cells through their key roles in metabolic processes. Recently, HDAC11 has been also been shown to have role in metabolic homeostasis [55][56][57] . The ability of the tested compounds to downregulate the metabolic genes through HDAC11 and Sox2 might be a feature that will enable these inhibitors to eliminate stem-like and non-stem-like cancer cells simultaneously.…”
Section: Discussionmentioning
confidence: 99%
“…More significantly, the knockout mice exhibited higher body temperature upon cold exposure, as well as higher UCP1 mRNA and protein expression levels in BAT in response to HFD treatment. Therefore, these data indicate that there was an overall enhancement of thermogenesis in the HDAC11 knockout mice (125).…”
Section: Hdac11mentioning
confidence: 58%
“…The lone member of class IV HDACs, HDAC11, was recently identified as a regulator of metabolic homeostasis (125). HDAC11-deficient mice were shown to be resistant to HFDinduced obesity and the metabolic syndrome (Figure 7A).…”
Section: Hdac11mentioning
confidence: 99%
“…Sun et al have demonstrated that knockout of HDAC11 in mice improved its resistance to metabolic syndrome and obesity by improving insulin sensitivity and glucose tolerance [ 60 ]. Studies by Bagchi et al also proved that the deletion of HDAC11 inhibited the HDAC11/BRD2 association, exacerbated brown adipose tissue formation, and enhanced insulin sensitivity HDAC11-KO mice when fed with a high-fat diet.…”
Section: Discussionmentioning
confidence: 99%